The private sector is already creating climate-smart value - Rosenstock, Todd S.; Lubberink, Rob; Gondwe, Sera; Manyise, Timothy; Dentoni, Domenico (2019)
However, the prevailing narrative suggests an endless search for inclusive business models that support a transition towards climate-smart agriculture (CSA). Our approach is a literature review of business models and CSA and qualitative fieldwork with four business models in Southern Africa to investigate the extent and way business models work to support CSA.